2017
DOI: 10.1038/s41598-017-05637-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of dopamine transporter to filopodia requires an outward-facing conformation of the transporter

Abstract: Dopamine transporter (DAT) has been shown to accumulate in filopodia in neurons and non-neuronal cells. To examine the mechanisms of DAT filopodial targeting, we used quantitative live-cell fluorescence microscopy, and compared the effects of the DAT inhibitor cocaine and its fluorescent analog JHC1-64 on the plasma membrane distribution of wild-type DAT and two non-functional DAT mutants, R60A and W63A, that do not accumulate in filopodia. W63A did not bind JHC1-64, whereas R60A did, although less efficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…W63 is essential for maintaining the network of intramolecular interactions supporting the OF conformation of DAT ( Penmatsa et al, 2013 ). Therefore, the W63A mutation results in narrowing the extracellular vestibule, which leads to the loss of substrate transport and cocaine binding, and a higher probability of an inward-facing (IF) conformation ( Chen et al, 2001 ; Ma et al, 2017 ; Sorkina et al, 2009 ). AIM-100 triggered the robust oligomerization and endocytosis of the W63A mutant but in this case endocytosis was unaffected by cocaine ( Figure 5F–H ).…”
Section: Resultsmentioning
confidence: 99%
“…W63 is essential for maintaining the network of intramolecular interactions supporting the OF conformation of DAT ( Penmatsa et al, 2013 ). Therefore, the W63A mutation results in narrowing the extracellular vestibule, which leads to the loss of substrate transport and cocaine binding, and a higher probability of an inward-facing (IF) conformation ( Chen et al, 2001 ; Ma et al, 2017 ; Sorkina et al, 2009 ). AIM-100 triggered the robust oligomerization and endocytosis of the W63A mutant but in this case endocytosis was unaffected by cocaine ( Figure 5F–H ).…”
Section: Resultsmentioning
confidence: 99%
“…24 ). Computational studies of the multimerization properties of members of the LeuT-fold family have revealed that (i) trimerization exploits the intrinsic ability of the LeuT architecture undergo a conformational change that pre-disposes the EL3 loop (LeuT) or H7 helix (the betaine transporter BetP) to make intermonomer contacts 36 , as observed for the BetP trimer 87 ; (ii) a variety of dimerization geometries that involve the scaffold domain are accessible to DAT 41 , and preferred oligomerization interfaces depend on the specific TM sequences and geometries 36 , such as the interfacial contacts of TM9 and TM12 in LeuT 12,13 , or TM12 in a SERT 39 ; (iii) the ability to oligomerize depends on the conformational state of the transporter 25 , which also affects its aggregation in selected localizations 88 ; and (iv) dimerization may facilitate the intrinsically accessible IF-OF transition 36 while promoting allostery 42 . Overall, these studies point to the possibility of stimulating the assembly of MATs into multimers or aggregates, the functional impact of which is yet to be established.…”
Section: Modulation Of Function By Small Moleculesmentioning
confidence: 98%
“…Inversely, oligomerization of both SERT and GAT1 is not influenced by various transporter substrates and inhibitors (23). In the case of hDAT, it has been observed that formation of the oligomeric complex is essential for correct trafficking of the transporter complex to the cell membrane (31, 33, 4043). (ii) Transporter oligomerization has been suggested to entail functional consequences (25, 44, 45) and to support the countertransport model of neurotransmitter transport (37), where amphetamine binds to one subunit of an SLC6 oligomer and the transporter-mediated efflux of neurotransmitter is subsequently performed by the neighboring subunit (46).…”
Section: Introductionmentioning
confidence: 99%